One and a half century of diffusion: Fick, Einstein, before and beyond - Philibert, Jean (Diffusion Fundamentals, 2005)
No Abstract in this version. an extended version with Abstract is in Vol. 4 (2006)6, see URL: https://diffusion-fundamentals.org/journal/4/2006/6.pdf